2020
DOI: 10.23887/jpi-undiksha.v9i4.28251
|View full text |Cite
|
Sign up to set email alerts
|

Learning Media Development of Analyzing Poetry-Building Element Using Sparkol Videoscribe

Abstract: This study aims to develop learning media to analyze the building blocks of poetry by using sparkol videoscribe in 10th grade students. This research is a development research (R&D). This research method is used to produce certain products, and test the effectiveness of these products. Data collection techniques used were interviews, questionnaires, and learning outcomes tests. The data analysis technique was carried out by analyzing the questionnaire which was seen from the results of the high and low per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In line with the results of research [42] that learning using videoscribe can improve students' critical thinking skills in mathematics significantly better than students who use power point media. So that learning using sparkol videoscribe affects student learning outcomes [43].…”
Section: Resultsmentioning
confidence: 99%
“…In line with the results of research [42] that learning using videoscribe can improve students' critical thinking skills in mathematics significantly better than students who use power point media. So that learning using sparkol videoscribe affects student learning outcomes [43].…”
Section: Resultsmentioning
confidence: 99%
“…After seeing and understanding the panel, the researcher found a solution so that the history learning process in the 2013 curriculum could run effectively. As researchers read in research conducted by Septianti et al (2020), Nafi'ah et al (2023, Farizi et al (2021), Williamson, (2023, entitled "Development of It-Based History Learning Media". In this research, he found a solution from previous research.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The model equipped with modules and guidelines is relatively new for most teachers in the North Luwu district so this innovation is very suitable to be applied to areas that are relatively the same as the needs of teachers in North Luwu District. According to Septianti et al, 2020, learning media is important to make learning process more effective and efficient (Septianti et al, 2020). Thus, Experiential Learning proved effective with learning media or modules (Normawati et al, 2021).…”
Section: Discussionmentioning
confidence: 99%